(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article is devoted to the problem of differentiation of households under the influence of active digitalization of their finances. It examines theoretical and practical approaches to the differentiation and classification of households, systematizes the criteria for their categorization. The article examines the existing methods of assessing the level of digitalization of finance, the indicators used. The author proposed a multifactorial system for assessing the degree of digitalization of household finances, gave examples of interpretation of the values obtained, noted the options for using the assessment system, as well as possible difficulties in implementing the proposed approach.